Shape effect on drying behavior of cement-based materials: Mechanisms and numerical analysis. (August 2018) - Samouh, Hamza; Rozière, Emmanuel; Loukili, Ahmed
Abstract: The shape of the specimen or structure has a direct impact on the behavior of drying concrete. This effect is not taken into account in most of shrinkage models and codes. Only the current B4 model and its previous version B3 model incorporate a shape factor. The determination of this coefficient is based on the nonlinear moisture diffusion analysis, which can explain the shape effect on the shrinkage rate. However, the model integrates this coefficient in the ultimate shrinkage values as well. An experimental study has been performed to confirm and understand this behavior. The mass loss and drying shrinkage of cylinders showed higher rate and ultimate values than the prisms, for the same effective cross section thickness. To explain this result, the drying, the differential shrinkage, the internal stress and the damaged depth were determined for both shapes through numerical modeling. The main input data of the model were the measured mass loss and shrinkage. The calculated desorption isotherm curve of the cylinder was below that of the prism, which is consistent with its higher ultimate mass-loss. The determination of stress profiles indicates slower stress mitigation for the cylinder. The cylinder develops a larger relative damaged area, defined as the part of the specimen where cracking is likely to occur due to tensile stresses. The results actually show that differential shrinkage between the edge and the core is more pronounced for the cylinder and decreases with time.